Empowering teachers: unveiling teacher leadership insights for independent learning curriculum implementation at secondary education units in Toraja Utara district - Hotmaulina Sihotang; Erni Murniarti; Yusak Yokoyama (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The urgency of this study to describe unveiling teacher leadership insights for independent learning curriculum implementation at secondary education units Method: This study uses a quantitative approach and is combined with a qualitative approach. The study population are 69 transformational teachers and the study sample are 69 transformational teachers. The study data were obtained through a questionnaire developed by researchers and reinforced by data obtained through in-depth interviews with school principals, vice principals in curriculum matters and teachers. This study questionnaire are leadership insights, the concept of transformational teachers and independent curriculum implementation. Quantitative data descriptive uses tools SPSS 26 to manage result, while qualitative data checks are valid and reliable using triangulation techniques and sources. The results showed that 58.94% of teachers already had insight into teacher leadership and 67.6% agreed to implement the independent curriculum. Reinforced through the results of interviews that the implementation of the independent curriculum is urgent to overcome learning loss and to produce graduates who fit the Pancasila students profile. Leadership insight, the concept of driving teachers in the implementation of the independent curriculum can be improved by providing opportunities for teachers to attend training and massively sharing the knowledge of driving teachers among fellow teachers to accelerate overcoming learning loss.